Comparison study on the extraction of moringa oleifera seeds oil by soxhlet and microwave methods - Mohd Syahiran, Yusuf (2015)
Extraction is a separation process and in this work, Moringa oleifera seeds oil was extracted using two methods soxhlet and microwave to find out the highest yield and best properties of oil extracted. For the soxhlet, approximately 40g of dry Moringa oleifera seeds are crushed and placed in a soxhlet extractor fitted with 1 L round bottom flask and a reflux condenser. Extraction took place one hour with 0.3 L n-hexane followed by removal of the solvent using rotary evaporator to get the Moringa oleifera oil. For the microwave, 800g of Moringa oleifera were placed in 1 L flat bottom flask. After adding 80 ml of solvent, the flask containing the sample was introduced to the microwave oven and adjusted with the condenser connected to a cold water recirculation system. The power, time and pressure of microwave was set as 600 W, 20 minute, and 65°C respectively. The oil collected from both methods was compared by measuring the properties such as acid no, pH, density and specific gravity (SG). For the soxhlet method, the acid no is 6.37 mgKOH, pH is 6, and density is 821.9 kg /m3 and SG of 0.8219. For the microwave method, the acid no is 5.80 mgKOH, pH is 6, and density is 590.7 kg /m3 and SG of 0.5907. As a conclusion, oil extracted by soxhlet method showed better yield and properties. This might be because n-haxane was used in microwave. Therefore, it is recommended to use methanol or any other polar solvent to compare between two methods.